2003
DOI: 10.1088/0031-9155/48/21/003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental results for 2D magnetic resonance electrical impedance tomography (MR-EIT) using magnetic flux density in one direction

Abstract: Magnetic resonance electrical impedance tomography (MR-EIT) is an emerging imaging technique that reconstructs conductivity images using magnetic flux density measurements acquired employing MRI together with conventional EIT measurements. In this study, experimental MR-EIT images from phantoms with conducting and insulator objects are presented. The technique is implemented using the 0.15 T Middle East Technical University MRI system. The dc current method used in magnetic resonance current density imaging is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 22 publications
0
62
0
Order By: Relevance
“…In previous MREIT experimental studies (10 -12), the biggest problems were object rotations inside the magnet to acquire the three components of the internal magnetic field data, and low SNR of reconstructed images. However, new MREIT reconstruction algorithms were recently introduced, along with phantom imaging results obtained without any object rotations (13)(14)(15).…”
Section: Magnetic Resonance Electrical Impedance Tomography (Mreit) Imentioning
confidence: 99%
See 1 more Smart Citation
“…In previous MREIT experimental studies (10 -12), the biggest problems were object rotations inside the magnet to acquire the three components of the internal magnetic field data, and low SNR of reconstructed images. However, new MREIT reconstruction algorithms were recently introduced, along with phantom imaging results obtained without any object rotations (13)(14)(15).…”
Section: Magnetic Resonance Electrical Impedance Tomography (Mreit) Imentioning
confidence: 99%
“…In previous MREIT experimental studies (10 -12), the biggest problems were object rotations inside the magnet to acquire the three components of the internal magnetic field data, and low SNR of reconstructed images. However, new MREIT reconstruction algorithms were recently introduced, along with phantom imaging results obtained without any object rotations (13)(14)(15).In this work we present some results of MREIT phantom imaging experiments performed with the harmonic B z algorithm and a 3.0 Tesla MRI system. After briefly introducing the fundamental principle of the conductivity image reconstruction algorithm, we present the experimental results of the conductivity imaging performance evaluation.…”
mentioning
confidence: 99%
“…However, in computer simulations, some undesirable side effects are observed which affect the accuracy of reconstructed images. Birgül et al (Birgül et al, 2003b) reported a MREIT phantom experiment using a two-dimensional (2D) reconstruction algorithm, which is based on the sensitivity matrix relation between conductivity and one component of magnetic flux distribution. İder and Onart (İder and Onart, 2004) reported a new MREIT algorithm using B z to reconstruct 3D conductivity distribution of the object.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous conductivity image reconstruction algorithms have been developed and most of them assume an isotropic conductivity distribution [5][6][7][8][9][10][11][12][13][14]. Almost all reported experimental MREIT studies using phantoms also have assumed isotropic conductivity distributions [8,13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all reported experimental MREIT studies using phantoms also have assumed isotropic conductivity distributions [8,13,15,16]. However, conductivities of certain biological tissues, for example white matters in the brain, are known to be anisotropic especially at low frequency.…”
Section: Introductionmentioning
confidence: 99%